’I do not want the public to feel unduly alarmed’. : turvallistamisargumentointi ja emotionaalinen retoriikka pääministeri Theresa Mayn puheissa terrori-iskujen jälkeen Britanniassa vuonna 2017 - Kärki, Veera (2021)
The United Kingdom experienced three devastating terrorist attacks in the spring of 2017. All three attacks were carried out by individuals linked to the extremist wing of the fundamentalist interpretation of Islam. The then- Prime Minister Theresa May gave speeches after each attack, in total four (one after each attack, two after the Manchester attack). In this bachelor thesis I analyse the securitization theory through rhetoric and emotional power in the argumentation of those four speeches. My research question is ‘how securitization arguments and emotional power are shown in May’s speeches and what values does May utilize in her rhetoric. The securitization theory by the Copenhagen School does not include emotions as a vital part of security studies or securitization theory. Nevertheless, emotions play a crucial role in the ways that a message is received by the public. A terrorist attack is a devastating experience to the public and the loved ones of the victims, as well as the society. Emotions and collective memory are necessary for the argument to become understood and accepted by the public. Securitization acts can be found unsuccessful if they do not resonate with peoples’ emotions and experiences through which things are perceived as important. I combine the securitization theory with social appraisal theory of emotions by Eric Van Rythoven in order to establish a connection between those aspects of security and rhetoric. Prime Minister May utilises powerful expressions in her speeches and partly lifts community and national values above the security actions. The wording and use of various pronouns create a fascinating combination of emotional rhetoric and securitization speech acts in all four speeches.